2017
DOI: 10.1038/srep45023
|View full text |Cite
|
Sign up to set email alerts
|

Post-Hoc Study: Intravenous Hydration Treatment in Chinese Patients with High Risk of Contrast-Induced Nephropathy Following Percutaneous Coronary Intervention

Abstract: Contrast-induced nephropathy (CIN) develops after the injection of iodinated contrast media. This is a post hoc analysis of the data obtained from the TRUST study, which was a prospective, multicentre, observational study conducted to evaluate the safety and tolerability of the contrast medium iopromide in patients undergoing cardiac catheterization from August 2010 to September 2011 in China, conducted to explore the current status, trends and risk predictors of hydration treatment. The status of hydration to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Except for GDF-15, Our logistic regression model showed that anemia, primary PCI and eGFR <90ml/min/1.73m 2 are also independent risk factors for CIN, which is coinciding with previous study[ 31 33 ]. Roman reported that anemia and renal dysfunction were predictors of CIN in patients undergoing primary PCI[ 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Except for GDF-15, Our logistic regression model showed that anemia, primary PCI and eGFR <90ml/min/1.73m 2 are also independent risk factors for CIN, which is coinciding with previous study[ 31 33 ]. Roman reported that anemia and renal dysfunction were predictors of CIN in patients undergoing primary PCI[ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Roman reported that anemia and renal dysfunction were predictors of CIN in patients undergoing primary PCI[ 34 ]. Other predictors for CIN include old age, hypertension, diabetes mellitus, high contrast dose, multi-vessel diseases, et al[ 31 33 ]. In our study, we didn’t find their predictive value of these predictors.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and basic research of CIN has become the hot spot currently. Hydration and maintenance of circulating volume are still the main measurement to prevent contrast nephropathy [ 9 ]. Clinical studies also showed that several drugs can prevent contrast nephropathy, including antioxidants ( N -acetylcysteine, statins), diuretic (furosemide), and vasodilators (such as calcium antagonists, dopamine, fenoldopam) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have explored the optimal hydration strategy [15][16][17], but the guidelines for patients with cardiac insufficiency still don't have specific hydration strategy recommendation, especially in patients with cardiac insufficiency [18]. The recommended prevention for CIN was routine hydration 12 hour before and 6-24 hour after the procedure with saline at regular speed(1 ml/kg/h or 0.5ml/kg/h for patients with NYHA>II or LVEF<35%).…”
Section: Figure 2 Discussionmentioning
confidence: 99%